If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + 8 = 20 + 3x Reorder the terms: 8 + 15x = 20 + 3x Solving 8 + 15x = 20 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 8 + 15x + -3x = 20 + 3x + -3x Combine like terms: 15x + -3x = 12x 8 + 12x = 20 + 3x + -3x Combine like terms: 3x + -3x = 0 8 + 12x = 20 + 0 8 + 12x = 20 Add '-8' to each side of the equation. 8 + -8 + 12x = 20 + -8 Combine like terms: 8 + -8 = 0 0 + 12x = 20 + -8 12x = 20 + -8 Combine like terms: 20 + -8 = 12 12x = 12 Divide each side by '12'. x = 1 Simplifying x = 1
| 4(2x-2y)+5(2y-x)= | | S=2(3.14159)r^2+2(3.14159)rh | | x^2+6x+10=5 | | 9-9a= | | .75x=20 | | -5+3x=-14 | | (lnx+1)(lnx-1)=0 | | -4(r+8)=-55 | | 8x-2(2x-3)=12+2x | | 7-5v=-4v | | 5(2x+1)-3(x-3)=63 | | x^2+19x+65=0 | | -9(-2w+3x-6)= | | 1=-7x | | 40+9-30+2= | | 15x+2=6x+10 | | 1059/10=18/1(14/13x) | | -1=-7x | | 6.2h-0.4=2.7 | | 3a+18=3(2a+3) | | X^2+12x-43=4x+5 | | -2=-7x | | -4x+6x^2+5x= | | -7.38=2.05-7.38 | | 4y+8=-2y+1 | | 24Y=72 | | 2.7+10m=7.23 | | 3a-3a^2= | | 2(x+4)+x=11 | | 16x+10=15x+2 | | 3=-4x-6 | | 1=10p |